Biobutanol production from oil palm frond juice in 2 L stirred tank bioreactor with in situ gas stripping recovery - N., Masngut; Faatihah, Mohamad Asri; Mior Ahmad Khushairi, Mohd Zahari (IOP Publishing, 2019)
Biobutanol has generated renewed interest of being a sustainable alternate fuel. As butanol can fully miscible with diesel fuel even at low temperatures, better fuel extender than ethanol, low vapour pressure, low miscibility with water and has higher price, making it most potential solvent compared to acetone and ethanol. Previous study shows that biobutanol can be biosynthesized from oil palm frond (OPF) juice by Clostridium acetobutylicum ATCC 824 in the lab scale experiment. Thus, this paper focused on the synthesis and characterization of the OPF juice as fermentation substrate for biobutanol production in 2 L batch fermentation using 50 g/L OPF juice. 14.0 g/L biobutanol was produced in batch fermentation. The research was further extended with fed-batch experiment and in situ gas stripping. 71.5% acetone, 36.5% biobutanol and 18.4% ethanol were stripped out from the fermentation broth during first gas stripping interval (42-48 h). After 120 h, total of 395 g/L biobutanol was stripped out. Thus, it was proven that OPF juice can be used as an alternative carbon source for biobutanol production while fed-batch fermentation with in situ gas stripping method improved the biobutanol production from OPF juice.